Isolation and Molecular Identification of Endophytic Bacteria of Clove Leaf (Syzygium aromaticum L) and Mechanism of Action Antibacterial - Sogandi Sogandi; Irviyani Irviyani; Usep Suhendar (Universitas Nusa Bangsa, 2022)
Endophytic bacteria are microorganisms that live in plant parts. Endophytic bacteria from clove (Syzygium aromaticum L.) leaves with antibacterial activity are rarely reported. Therefore, this study aims to isolate endophytic bacteria from clove leaves (Syzygium aromaticum L.), screen and determine potential endophytic bacteria as antibacterial compounds, identify molecularly with 16S rRNA, analyze bacterial growth curves and detect bioactive compounds produced by potential bacteria. Endophytic bacteria were isolated as many as 7 pure isolates including IRV1, IRV2, IRV3, IRV4, IRV5, IRV6, IRV7. IRV3 isolates showed the most dominant activity in inhibiting the growth of test bacteria and as the most potential producer of antibacterial compounds. Molecular identification with PCR (polymerase chain reaction) amplification in the 16S rRNA gene showed IRV3 isolate as Staphylococcus sp. with a 99% similarity value. Besides, the results of GCMS analysis of secondary metabolites of IRV3 isolates showed pyrazine content as a dominant compound, which has been known as a bioactive compound in inhibiting bacterial growth. Therefore, the results of this study revealed that IRV3 isolates that were successfully isolated and identified would be able to contribute to further research to find new antibiotic sources.Keywords: Antibacterial, Endophytic, Clove Leaves, Bioactive, Syzygium aromaticumIsolasi dan Identifikasi Molekuler Bakteri Endofit Daun Cengkeh (Syzigium aromaticum L) dan Mekanisme Aksinya Sebagai AntibakteriABSTRAKBakteri endofit adalah mikroorganisme yang hidup di dalam bagian tanaman. Bakteri endofit dari daun cengkeh (Syzygium aromaticum L.) dengan aktivitas antibakteri masih jarang dilaporkan. Oleh karena itu, penelitian ini bertujuan untuk mengisolasi bakteri endofit dari daun cengkeh (Syzygium aromaticum L.), skrining dan menentukan bakteri endofit potensial sebagai penghasil senyawa antibakteri, mengidentifikasi secara molekuler dengan 16S rRNA, menganalisis kurva pertumbuhan bakteri dan mendeteksi senyawa bioaktif yang diproduksi oleh bakteri potensial. Bakteri endofit yang berhasil diisolasi sebanyak 7 isolat murni diantaranya IRV1, IRV2, IRV3, IRV4, IRV5, IRV6, IRV7. Isolat IRV3 menunjukkan aktivitas yang paling dominan dalam menghambat pertumbuhan bakteri uji dan sebagai penghasil senyawa antibakteri yang paling potensial. Identifikasi molekuler dengan amplifikasi PCR (polymerase chain reaction) pada gen 16S rRNA menunjukkan isolat IRV3 sebagai Staphylococcus sp. dengan nilai similaritas 99%. Selain itu, hasil analisis GCMS dari metabolit sekunder isolat IRV3 menunjukkan kandungan pirazin sebagai senyawa dominan, yang telah dikenal sebagai senyawa bioaktif dalam menghambat pertumbuhan bakteri. Oleh karena itu, hasil penelitian ini mengungkapkan bahwa isolate IRV3 yang berhasil diisolasi dan diidentifikasi akan dapat berkontribusi pada penelitian lebih lanjut untuk menemukan sumber antibiotik baru.Kata kunci: antibakteri, endofit, daun cengkeh, bioaktif, Syzigium aromaticum